The Effect 0f Problem Solving Method on Motivation and Learning Mathematic Results of Class V Sdn 29 Saok Laweh Kabupaten Solok - Trisno Trisno; Risda Amini; Irdamurni Irdamurni (International Journal of Educational Dynamics, 2019)
The learning process in the classroom is still dominated by conventional teaching, teachers was seldom to invite and provide opportunities for students to interact, collaborating or cooperating with their classmates. This problem like this can give an impression to students that math lessons are boring and scary. The purpose of this research is to get information about the effect of student learning outcomes who teach by using problem solving methods with the motivation of students who teach by using conventional methods in learning mathematics in class V SDN 29 Saok Laweh Kabupaten Solok. The design of the research is quasy experiment. The population is all fifth grade students that consist of 2 classes with 48 people. Sampling was gathered by random sampling technique. The research data was collected using the initial ability test and final ability test. The results of the research that found the learning outcomes of students who teach by using problem solving methods had better that students’ learning motivation learning outcomes who teach by using conventional methods with a tcount is 1.984 greater than ttable that found 4.72 with a real level of α = 0.05. Calculation results in the table using the Ftest can found Fcount are 4.258. Furthermore, Ftable is found 4.11. It can be concluded that there are differences in students’ learning outcomes who teach by using problem solving methods with students’ learning outcomes who teach by using conventional methods. It means that there are differences in motivation of students teach using problem solving methods with motivation of students who teach by using conventional methods in learning mathematics in Class V SD Negeri 29 Saok Laweh Kecamatan Kubung.